Lives before and after Stonehenge: An osteobiographical study of four prehistoric burials recently excavated from the Stonehenge World Heritage Site. (August 2018) - Mays, S.; Roberts, D.; Marshall, P.; Pike, A.W.G.; van Heekeren, V.; Bronk Ramsey, C.; Dunbar, E.; Reimer, P.; Linscott, B.; Radini, A.; Lowe, A.; Dowle, A.; et al.
Abstract: Osteobiographies of four individuals whose skeletal remains were recovered in 2015–16 from the Stonehenge World Heritage Site are constructed, drawing upon evidence from funerary taphonomy, radiocarbon dating, osteological study, stable isotope analyses, and microscopic and biomolecular analyses of dental calculus. The burials comprise an adult from the Middle Neolithic period, immediately prior to the building of Stonehenge, and two adults and a perinatal infant dating from the Middle Bronze Age, shortly after the monument ceased to be structurally modified. The two Middle Bronze Age adults were closely contemporary, but differed from one another in ancestry, appearance and geographic origin (key components of ethnicity). They were nevertheless buried in very similar ways. This suggests that aspects they held in common (osteological analysis suggests perhaps a highly mobile lifestyle) were more important in determining the manner of deposition of their bodies than any differences between them in ethnicity. One of these individuals probably came from outside Britain, as perhaps did the Middle Neolithic adult. This would be consistent with the idea that the Stonehenge landscape had begun to draw people to it from beyond Britain before Stonehenge was constructed and that it continued to do so after structural modification to the monument had ceased. Highlights: Study of 4 prehistoric burials recently excavated from Stonehenge World Heritage Site. Osteobiographies are crafted for each individual. The group included individuals with both local and more distant origins. Ethnicity may have been less important than lifestyle in determining burial practice. The role of osteobiography in bioarchaeology is considered.